Strategi Kebijakan Implementasi Eko-Teologi di Institut Agama Kristen Negeri (IAKN) Toraja - Yulianti Duma (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy examines the fundamental problems in the implementation of eco-theology at the State Christian Institute (IAKN) Toraja, namely the absence of a formal policy framework at the institutional level and the absence of integrated implementation guidelines. This condition causes efforts related to eco-theology to be partial, unstructured, and unmeasurable, thus limiting the institution's contribution to environmental conservation issues. Based on a policy analysis using William N. Dunn's scoring theory, it was found that